The non-homologous end-joining pathway of S. cerevisiae works effectively in G1-phase cells, and religates cognate ends correctly and non-randomly - Gao, Shujuan (DNA Repair (Amst), 2016)
DNA double-strand breaks (DSBs) are potentially lethal lesions repaired by two major pathways: homologous recombination (HR) and non-homologous end-joining (NHEJ). Homologous recombination preferentially reunites cognate broken ends. In contrast, non-homologous end-joining could ligate together any two ends, possibly generating dicentric or acentric fragments, leading to inviability. Here, we characterize the yeast NHEJ pathway in populations of pure G1 phase cells, where there is no possibility of repair using a homolog. We show that in G1 yeast cells, NHEJ is a highly effective repair pathway for gamma-ray induced breaks, even when many breaks are present. Pulsed-field gel analysis showed chromosome karyotypes following NHEJ repair of cells from populations with multiple breaks. The number of reciprocal translocations was surprisingly low, perhaps zero, suggesting that NHEJ preferentially re-ligates the “correct” broken ends instead of randomly-chosen ends. Although we do not know the mechanism, the preferential correct ligation is consistent with the idea that broken ends are continuously held together by protein-protein interactions or by larger scale chromatin structure.